Strategi Petani Gurem Dalam Penanggulangan Kemiskinan Melalui Permintaan Kredit Di Kabupaten Kampar Provinsi Riau - Caska (Jurnal Ekonomi, 2010)
The research is purposed to understand the factor determining a credit demand and the efficiency level of the user of production factor. The research method used is the explanatory survey method. We have 120 level scale farmers of oil palm as the customers, consisting of 60 customers in both Mandiri bank and KUD. The results shows that: first, there is a connection according to a credit demand,we will have the level elasticity of interest rate of credit as -0.248; the elasticity of administration expense as 0.217; the elasticity of permanent income as 0.739; and the elasticity of transitory income as 0.077. Second, the factor of workforce productivity in the decreasing returns to scale position, means that the amount of oil palm production will increase with lower proportion than the increase of work force expanse; and the financial capital factor in the increasing returns to scale means that the amount of oil palm production will increase with a higher proportion than the increase of financial capital.